Коливна динаміка домішкових нанокомплексів при формуванні терагерцових смуг нелінійно-оптичного підсилення у кварцових волокнах - Сердега, Ірина Володимирівна; Serdeha, I.V. (Харків : Харківський національний університет імені В. Н. Каразіна, 2020)
Дисертаційна робота присвячена експериментальним дослідженням нелінійного оптичного підсилення світла та числовому моделюванню коливної динаміки домішкових нанокомплексів, яка формує профілі ВКР підсилення світла в різних типах одномодових волокон на основі кварцового скла. Актуальність теми у даний час обумовлена підвищеним інтересом до аналізу фізичних особливостей індивідуального та колективного впливу фононних коливань у серцевині волокон, які власне визначають ефективність підсилення оптичних сигналів за допомогою вимушеного комбінаційного розсіяння світла. В роботі проаналізовано наявні експериментальні дані вимірювання підсиленого спонтанного випромінювання за схемою із зустрічною накачкою кварцового одномодового волокна в області 1420 нм…1650 нм. В роботі вперше запропоновано методику кількісного визначення величини індивідуального зсуву довжини хвилі ЛД накачки від інтенсивності його випромінювання.

The dissertation is devoted to experimental research of nonlinear optical amplification of light in singlemode fibers based on the silica glass and it contained the numerical modeling of oscillatory dynamics of doping nanocomplexes, which forms the Raman gain profiles of light in the different types of singlemode fibers based on the sislica glass. Actuality currently due to increased interest in analyzing physical characteristics of individual and collective influence of phonon vibrations in the fiber core that really determine the gain effectiveness of optical signals using stimulated Raman effect. The available experimental data of measurement of amplified spontaneous emission (ASE) using to the counter-pumping scheme in the silica singlemode fiber at the region of 1420 nm…1650 nm are analyzed; the peculiarities of the oscillatory dynamics of impurity nanocomplexes on the formation of optical amplification due to stimulated Raman effect by multimode decomposition in several types of silica fibers have been studied. The method of separation onto stimulated and spontaneous parts in the measured ASE spectra was improved. The Gaussian filtering technique of the measuring equipment noises at ASE registration in the idling mode of the nonlinear optical amplifier is developed. For the first time the quantitative determination technique of values of individual pumping LD wavelength shifts as function of its radiation intensity is offered in this work.
Oscillatory dynamics of doping nanocomplexes at the terahertz bands formation of nonlinear optical amplification in silica fibers
Keywords: NATURAL SCIENCES::Physics::Other physics::Optics; нелінійні оптичні явища; хвилі в активних середовищах; квантові генератори і підсилювачі; фотон-фононна взаємодія; коливна динаміка; молекулярні нанокомплекси; оптичне підсилення; nonlinear optical phenomena; waves in active media; quantum generators and amplifiers; photon-phonon interaction; oscillatory dynamics; molecular nanocomplexes; optical amplification; Raman gain profile; forced Raman scattering